Negotiating legal pluralism: Sharia and Civil Law integration in Brunei Darussalam - Muhammad Nur; Ibnor Azli Ibrahim; Siti Maymanatun Nisa; Muhammad Adib Alfarisi; Dedy Afriadi (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study critically examines the integration of Sharia and civil law in Brunei Darussalam, focusing on institutional frictions, normative conflicts, and the challenges of balancing Islamic legitimacy with social cohesion. The research analyses structural tensions within the dual legal system and proposes actionable solutions to strengthen coherence and public trust. Employing a qualitative methodology that comprises document analysis, expert interviews, and case studies, the study examines the functioning pattern of coexistence between Sharia and civil law in practice and its implications for legal stakeholders. The findings reveal that the integration process generates structural ambiguities, overlapping jurisdictions, and uneven societal acceptance, particularly among women and non-Muslim minorities. These issues highlight the need for targeted reforms to ensure fairness and inclusivity. The study concludes that sustainable integration requires concrete steps: harmonising the Shariah Penal Code Order 2013 with the Civil Penal Code, revising discriminatory provisions in family law, and developing a Joint Judicial Guideline to clarify jurisdictional boundaries between Syariah and civil courts. By advancing these recommendations, the research emphasises that inclusive policy dialogue and cross-institutional collaboration must culminate in substantive legal reforms rather than rhetorical commitments. In doing so, it contributes to broader debates on Islamic legal reform and governance in Muslim-majority countries that are facing similar dynamics.